Hubungan Persepsi Siswa Terhadap Pelajaran Matematika Dengan Hasil Belajar Matematika Kelas V SD Negeri Percontohan Kabanjahe - Robenhart Tamba; Eybi Asrina Br Ginting (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to find out whether there is a relationship between students' perceptions of Mathematics lessons and the learning outcomes of Mathematics in fifth grade at SD Negeri Pilot Kabanjahe in the Academic Year 2022/2023. The type of research used is quantitative. The subjects used as the sample in this study were 26 students. While the data collection technique uses a questionnaire on students' perceptions of Mathematics lessons, and documentation of students' Mathematics learning outcomes. The data analysis used is product moment correlation analysis, to find out whether there is a correlation in student perceptions of fifth grade Mathematics at SD Negeri Pilot Kabanjahe in the 2022/2023 academic year.The results of this study are: 1) seen from the calculation of descriptive statistical analysis that students' perceptions of fifth grade mathematics at SD Negeri Pilot Kabanjahe for the 2022/2023 academic year are obtained in the moderate category (69.3%). 2) student learning outcomes in the moderate category (96.2%). 3) there is a positive and significant correlation between students' perceptions of Mathematics and the Mathematics learning outcomes of fifth grade students at SD Negeri Pilot Kabanjahe for the 2022/2023 Academic Year with a significant value of 5% of 0.404 and a positive Pearson correlation value of 0.578 with the degree of closeness of the relationship between the two low.